STUDI LITERATUR: PERAN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH DASAR - Eka Ulfiani; Jakaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to comprehensively analyze the role of educational facilities and infrastructure (sarpras) in supporting the improvement of learning quality in primary schools through a literature review approach. Facilities and infrastructure are essential components of the National Education Standards (SNP) that directly affect the effectiveness of the teaching and learning process. The review finds that the availability and quality of educational facilities are closely related to student engagement, learning motivation, and academic achievement. However, challenges such as unequal distribution, limited funding, and low stakeholder involvement remain significant barriers to achieving equitable education quality. Therefore, a collaborative and sustainable strategy involving the government, educational institutions, communities, and the private sector is needed in the planning, procurement, and management of educational facilities to ensure the realization of equitable and high-quality primary education.